Ritual vocabulary in Ukrainian dialects of Western Kuban in the ethno-linguistic aspect (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with the ethno-linguistic analysis of the lexemes representing Kuban marriage rite compared with Ukranian linguoculture. The comparison of the primary rite tradition with the secondary rite tradition allows to reveil the mechanisms the newly developed culture is formed. Also it helps to find out the culture paradigm shift and the axiological system changes in the rite represented in verbal and symbolic rite code.
Keywords: marriage rite terminology; mechanisms developing new local culture; ethno-linguistic analysis